2012
DOI: 10.4103/1463-1741.99887
|View full text |Cite
|
Sign up to set email alerts
|

Noise and hand-arm vibration exposure in relation to the risk of hearing loss

Abstract: The aim of this study was to examine the possible association of combined exposure of noise and hand-arm vibration (HAV) and the risk of noise-induced hearing loss. Workers in a heavy engineering industry were part of a dynamic cohort. Of these workers, 189 had HAV exposure, and their age and hearing status were recorded in the same year and were, therefore, included in the analysis. Data on HAV duration and acceleration was gathered through questionnaires, observations, and measurements. All available audiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
2
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 23 publications
(51 reference statements)
2
24
2
4
Order By: Relevance
“…One could also speculate that the higher prevalence is due to simulations exposure to HAV. One earlier longitudinal study suggested an increased risk of hearing loss from HAV in a noisy environment, [9] but this conclusion is not supported by other longitudinal studies. [ 1,13] There were 29 cases of WF among the participants in this study.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…One could also speculate that the higher prevalence is due to simulations exposure to HAV. One earlier longitudinal study suggested an increased risk of hearing loss from HAV in a noisy environment, [9] but this conclusion is not supported by other longitudinal studies. [ 1,13] There were 29 cases of WF among the participants in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Earlier longitudinal and cross-sectional studies have found an increased risk of hearing loss among workers with VWF compared to workers without VWF who have similar noise exposure and are of similar age. [1,[5][6][7][8][9] Therefore, WF from exposure to HAV might be a factor that increases the risk of noise-induced hearing loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 476 audiograms measured between 1987 and 2008 were collected and classified according to Klockhoff et al [] for both the left and right ear [Pettersson et al, ]. The Klockhoff method [] was used because the audiometric measurements did not register hearing threshold levels (HL) with higher sensitivity than 10 dB HL.…”
Section: Methodsmentioning
confidence: 99%
“…Findings from a Finnish study [Pyykko et al, ; Starck et al, ] on the simultaneous exposure to HAV and noise and the risk of developing hearing loss did not find an increased risk of hearing loss from noise exposure when HAV was present. In contrast, a study on a Swedish cohort did find an increased risk of hearing loss with increased exposure to noise when HAV exposure was present [Pettersson et al, ]. Moreover, Pyykko et al [] conducted a longitudinal study on forestry workers with or without VWF who had similar noise exposure and compared their hearing.…”
Section: Introductionmentioning
confidence: 99%